Protein targeting and integration signal for the chloroplastic outer envelope membrane. - Li, H M (1996)
Most proteins in chloroplasts are encoded by the nuclear genome and synthesized in the cytosol. With the exception of most quter envelope membrane proteins, nuclear-encoded chloroplastic proteins are synthesized with N-terminal extensions that contain the chloroplast targeting information of these proteins. Most outer membrane proteins, however, are synthesized without extensions in the cytosol. Therefore, it is not clear where the chloroplastic outer membrane targeting information resides within these polypeptides. We have analyzed a chloroplastic outer membrane protein, OEP14 (outer envelope membrane protein of 14 kD, previously named OM14), and localized its outer membrane targeting and integration signal to the first 30 amino acids of the protein. This signal consists of a positively charged N-terminal portion followed by a hydrophobic core, bearing resemblance to the signal peptides of proteins targeted to the endoplasmic reticulum. However, a chimeric protein containing this signal fused to a passenger protein did not integrate into the endoplasmic reticulum membrane. Furthermore, membrane topology analysis indicated that the signal inserts into the chloroplastic outer membrane in an orientation opposite to that predicted by the "positive inside" rule.